Blockade of lymphocyte trafficking in inflammatory bowel diseases therapy: importance of specificity of endothelial target. (July 2014) - Allocca, Mariangela; Fiorino, Gionata; Vermeire, Severine; Reinisch, Walter; Cataldi, Fabio; Danese, Silvio
<x xml:space="preserve">Abstract</x> Inflammatory bowel diseases (IBD) are chronic, relapsing to continuously active inflammatory disorders of the gastrointestinal tract, of potentially destructive nature. So far, the excessive and/or unbalanced immune response has been the target of the majority of the IBD treatments. Despite the increasing use of immunosuppressants and anti-TNF-α inhibitors, about 30% of patients with Crohn's disease and about one-tenth of patients with ulcerative colitis still require major abdominal surgery at 5–10 years. As a result, new therapeutic approaches are urgently needed. The endothelium has a key role in the development of the inflammation, as it selectively governs the leukocyte trafficking and the influx of leukocytes into the intestinal mucosa. Drugs blocking such crossing, specifically at intestinal level, are going to be a new therapeutic option in IBD.